Clonal hematopoiesis in patients with autoimmune thrombocytopenia: an international multicenter study - Bruno Fattizzo; Alfredo Marchetti; Alessandro Bosi; Carmelo Gurnari; Juri Alessandro Giannotta; Giacinto Luca Pedone; Elena Rossi; Valentina Carrai; Andrea Guido; Filippo Brioschi; Monica Carpenedo; Monica Crugnola; et al. (Blood Advances)
Abstract: Diagnostic boundaries between immune thrombocytopenia (ITP) and other thrombocytopenic states, such as thrombocytopenic myelodysplastic syndromes, may be difficult to establish, and the detection of somatic mutations by next-generation sequencing (NGS) may be of aid. Here, we aimed at characterizing the prevalence and clinical significance of clonal hematopoiesis in ITP. In this multicentric retrospective observational study, we enrolled 167 adult patients with ITP, followed at 13 centers in Italy, United Kingdom, and the United States. Patients underwent NGS evaluation after a median of 3.6 years from ITP onset, and 83% had received at least 1 therapy line, for a median of 2 lines (range, 0-9); 51 of 167 patients (30%) had at least 1 mutation. After exclusion of germ line variants and polymorphisms, 31 of 167 (18.5%) were defined as having clonal hemopoiesis. Most commonly mutated genes were TET2, DNMT3A, SRSF2, and ASXL1 (median variant allele frequency, 29%); 19 of 31 patients (68%) had high-risk variants, and 8 had multiple mutations. Mutated patients were more frequently older males and showed a shorter time from first to second-line therapy, particularly with thrombopoietin receptor agonist (TPO-RA). Additionally, clonal hematopoiesis was associated with increased thrombotic risk (26% vs 8% in NGS-negative cases; P = .01), independently from TPO-RA exposure, though with an age effect. These data demonstrated the prevalence of clonal hematopoiesis in 18% of adult patients with ITP, which is associated with older age, relapsed/refractory disease, and high risk of thrombotic complications.